2022
DOI: 10.1126/sciadv.abo5387
|View full text |Cite
|
Sign up to set email alerts
|

Protein diffusion in Escherichia coli cytoplasm scales with the mass of the complexes and is location dependent

Abstract: We analyze the structure of the cytoplasm by performing single-molecule displacement mapping on a diverse set of native cytoplasmic proteins in exponentially growing Escherichia coli . We evaluate the method for application in small compartments and find that confining effects of the cell membrane affect the diffusion maps. Our analysis reveals that protein diffusion at the poles is consistently slower than in the center of the cell, i.e., to an extent greater than the confining effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(129 citation statements)
references
References 76 publications
3
119
0
Order By: Relevance
“…Previous work by others has shown that the cytosolic diffusion rate of proteins scales with molecular weight, but not according to the Stokes-Einstein equation, which stipulates that D ∝ (Molecular Weight) -1/3 . Instead, a D ∝ (Molecular Weight) -2/3 scaling has been observed by others independently for different proteins(4548). Here, we obtain a D ∝(Molecular Weight) -0.71 scaling when plotting the measured diffusion coefficients against the molecular weights of monomeric eYFP and the protein complexes discussed above (likely stoichiometries were estimated based on current biophysical models of the cytosolic injectisome protein complexes) (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Previous work by others has shown that the cytosolic diffusion rate of proteins scales with molecular weight, but not according to the Stokes-Einstein equation, which stipulates that D ∝ (Molecular Weight) -1/3 . Instead, a D ∝ (Molecular Weight) -2/3 scaling has been observed by others independently for different proteins(4548). Here, we obtain a D ∝(Molecular Weight) -0.71 scaling when plotting the measured diffusion coefficients against the molecular weights of monomeric eYFP and the protein complexes discussed above (likely stoichiometries were estimated based on current biophysical models of the cytosolic injectisome protein complexes) (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Size- and position-dependency had previously been reported for the diffusion of smaller components in different cells. They were attributed to properties such as the hierarchy of cytoplasm pore sizes (33), glass-like transitions of bulk material (15), or to heterogeneities across cells (16). Our data for large objects, support a different physical origin, in which both size and position dependency can emerge solely from hydrodynamic interactions with the surface.…”
Section: Discussionmentioning
confidence: 99%
“…These have shown that cytoplasm response will depend on time-scale, force amplitude or component size (9)(10)(11)(12)(13). The question of object size has notably raised important notions for cytoplasm mechanics, as for components smaller or larger than a typical mesh size, the cytoplasm may exhibit different rheological signatures ranging from fluid, to viscoelastic, poroelastic, or even glassy materials (14)(15)(16)(17)(18)(19). However, these studies were restricted to regimes of relatively small objects typically below the micron size, as well as low forces and displacement amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Cell components compartmentalize by demixing or preferential interactions in which protein crowders assemble with other biomolecules or membranes. Indeed, diffusion experiments have shown significant spatial heterogeneity in prokaryotes and eukaryotes 8,9 . Crowders captured in large complexes crowd less effectively because a crowder needs to diffuse to generate the depletion force, and complexation reduces the crowder number density.…”
Section: Introductionmentioning
confidence: 99%
“…These probes are based on diffusion or protein conformation. The former measures viscosity, which, among others, depends on the relative size of the tracer and crowders and is sensitive to large immobile obstacles such as a membrane 9,11 . Conformationally-sensitive probes rely on compressing a probe protein 12,13 .…”
Section: Introductionmentioning
confidence: 99%